THE CULTURAL NEGOTIATION OF BEING SHIA AND MADURESE: How It Can be Reconciled? - Abdus Sair; Yelly Elanda (Islamuna: Jurnal Studi Islam, 2021)
The life of the Sampang Shia community in the refugee camps remains regretful. They are considered a heretical sect by the Indonesian Council of Religious Scholars (MUI), expelled and face complex social problems. Various policies have been attempted, but have not had an impact. This article aims at explaining the reasons for the emergence of discrimination and expulsion of the Sampang Shia community and how they negotiated as a hated Shia minority as well as a “good” Madurese community. Can they be reconciled? This article was written based on field research using a qualitative method with a narrative approach. The data were obtained by conducting in-depth interviews with leaders or figures as well as Shia refugees in the refugee camps. This article shows that the Shia community of Sampang was expelled because of a deviant discourse produced by the MUI. Meanwhile, their negotiation as Shia they hate is to remain a good Madurese; obey the kiai, continue to speak Madurese, continue to work as a cultural spirit, and continue to live life while looking for a cultural way back. [Kehidupan masyarakat Syiah Sampang di kamp pengungsian tetap disesalkan. Mereka dianggap aliran sesat oleh Majelis Ulama Indonesia (MUI), diusir dan menghadapi masalah sosial yang kompleks. Berbagai kebijakan telah diupayakan, namun belum berdampak. Artikel ini bertujuan untuk menjelaskan alasan munculnya diskriminasi dan pengusiran komunitas Syiah Sampang dan bagaimana mereka bernegosiasi sebagai minoritas Syiah yang dibenci sekaligus komunitas Madura yang “baik”. Bisakah mereka berdamai? Artikel ini ditulis berdasarkan penelitian lapangan dengan menggunakan metode kualitatif dengan pendekatan naratif. Data diperoleh dengan melakukan wawancara mendalam dengan tokoh atau tokoh serta pengungsi Syiah di tempat pengungsian. Artikel ini menunjukkan bahwa komunitas Syiah Sampang diusir karena wacana menyimpang yang dihasilkan oleh MUI. Sedangkan negosiasi mereka sebagai Syiah yang mereka benci adalah tetap menjadi orang Madura yang baik; taat pada kiai, terus berbahasa Madura, terus berkarya sebagai spirit budaya, dan terus menjalani kehidupan sambil mencari jalan kebudayaan untuk kembali]